Basic Requirements for Sentences. Legality of Sentences (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the basic requirements for sentences, the legality of sentences from the perspective of criminal procedural law, ensuring the legality of sentences through the impartiality of the judge, issues related to conducting proceedings within the framework of the law, ensuring fair trial based on the equality of citizens before the law and the court, respecting the dignity and honor of the individual, protecting the rights and freedoms of citizens, the public hearing of criminal cases in court, the adversarial nature of proceedings, and the strict adherence to principles of directly and orally examining evidence.